Messengers and Social Networks as an Auxiliary Means of Teaching a Foreign Language to Students of Non-Linguistic Majors - Stella R. Gartung (Виртуальная коммуникация и социальные сети)
Modern linguistic didactics focuses on the efficiency of the existing methods of teaching a foreign language while looking for new digital means. The article reviews the use of messengers and social networks as a modern auxiliary means in teaching a foreign language, especially to students of non-linguistic majors. Social networks are able to immerse the student in the linguistic environment through the means of Internet communication, Internet memes, emojis, etc. They provide interactive tools that simulate routine and professional communicative situations. Messengers also provide an opportunity for real-time academic communication. By integrating media applications in the academic routine, teachers employ a personal-activity approach to develop soft skills and self skills. This approach offers authentic relevant materials, modern vocabulary, and a convenient accessible format. It also reduces stress level and enables simultaneous mastering of information, communication, and professional competencies while increasing motivation for learning a foreign language.